а)(-9;3)
b)(-&;0) (5;+&)
c)(-10;10)
Объяснение:
a)
(x+9)(x-3)<0
X^2-3x+9x-27<0
X^2+6x-27=0
D=36+4*27*1=144
X1=(-6+12)/2=3
X2=(-6-12)/2=-9
ответ:(-9;3)
b)x - 13/x + 8 > 0;
x^2-13x+8x=0
X^2-5x=0
X(x-5)=0
X1=0 x-5=0
x2=5
ответ :(-&;0) (5;+&)
С) х³ − 100х < 0.
X^2=t
t^2-100=0
t^2=100
t=+-10
ответ :(-10;10)
а)(-9;3)
b)(-&;0) (5;+&)
c)(-10;10)
Объяснение:
a)
(x+9)(x-3)<0
X^2-3x+9x-27<0
X^2+6x-27=0
D=36+4*27*1=144
X1=(-6+12)/2=3
X2=(-6-12)/2=-9
ответ:(-9;3)
b)x - 13/x + 8 > 0;
x^2-13x+8x=0
X^2-5x=0
X(x-5)=0
X1=0 x-5=0
x2=5
ответ :(-&;0) (5;+&)
С) х³ − 100х < 0.
X^2=t
t^2-100=0
t^2=100
t=+-10
ответ :(-10;10)